A cross-sectional study to determine prevalence of obesity in high income group colonies of Gwalior city - Tiwari Ranjana; Srivastava Dhiraj; Gour Neeraj (Wolters Kluwer Medknow Publications, 2009)
Background: Obesity has become a major chronic disorder affecting the larger population more than any other disease in the world. Objectives: 1) To determine the prevalence of obesity in both sexes in persons aged 30 years and above. 2) To determine the relationship of epidemiological determinants on the obesity status in the study subjects. Materials and Methods: The present study had been undertaken in literate high income group colonies of Gwalior city in which persons aged 30 years and above, in a family, were interviewed. A house-to-house survey method on a pre-designed, pre- tested structured questionnaire was used. Information regarding socio-demographic profile, eating habits and current health status were recorded. Anthropometric data regarding height, weight and blood pressure was also taken. The data was collected and analyzed using statistical software and chi square and proportional statistical test were applied. Results: The study showed that 34.4% of males and 31.3 % of females, both aged 30years and above were either obese or over weight. There was a statistically significant difference noted in the likening of fried food and fast food between obese and overweight persons and persons with normal body mass index. Conclusions: It can be concluded from the present study that obesity is a chronic illness. Early detection of it can prevent various complications associated with it. BMI plays a crucial role in its early detection as it is simple to calculate and can even detect the pre-obesity stage in time.